Effectiveness of Empirical Hormonal Stimulation in the Treatment of Idiopathic Oligoasthenoteratospermia: A Clinical Evaluation - Akhmais, Abeer Ahmed; Thaar, Dhari Khamees; Mohammed Ali, Ali Nabeel; Al-Hamadani, Marwah Ayad (Journal of Neonatal Surgery, 2025)
Background: Instead of distinct forms, DNA fragmentation and chromatin structural abnormalities are connected to most occurrences of idiopathic oligoasthenoteratospermia (OAT). Hormonal treatment dosage and duration varies amongst proposed strategies. Testicular testosterone (TT), which is transformed into dihydrotestosterone (DHT), and gonadotropins are stimulated by gonadotropin-releasing hormone (GnRH) pulses. DHT raises the concentration of TT for spermatogenesis via promoting the synthesis of androgen-binding protein (ABP) in Sertoli cells. Aim: to assess how well sperm parameters (such as count, motility, and morphology) are improved by empirical hormonal stimulation. Subjects And Methods: The study included a sample of 15 male patients diagnosed with idiopathic oligoasthenoteratospermia. These patients were selected conveniently from those attending the infertility clinic at AL-Yarmouk –Teaching Hospital. Results: Sperm concentration increased slightly from 5.334 ± 1.794 × 106/ml before treatment to 6.067 ± 1.885 × 106/ml after treatment, and the percentage of normal sperm morphology increased from 0.933% ± 1.1 before treatment to 3.6% ± 8.781 after treatment (P = 0.002). Prior to therapy, the total sperm count was 13.794 ± 3.374 × 106/ml; following treatment, it increased to 17.156 ± 9.225 × 106/ml (P = 0.042). Conclusion: The percentage of normal sperm morphology increased significantly after hormonal treatment (P = 0.002). Sperm quality improved as evidenced by a significant drop in aberrant sperm shapes (P = 0.049).